Please help! I can't figure out a solution for this problem:

6. Create an equation, using factored expressions, that has 53 and 22 as its only solutions.

Thank you in advanced for everyone's help!

-Red Glasses

Expand the following: (x - 22) (x - 53)

(x - 22) (x - 53) = (x) (x) + (x) (-53) + (-22) (x) + (-22) (-53): x x - 22 x - 53 x - 22 (-53)

x x = x^2: x^2 - 22 x - 53 x - 22 (-53)

-22 (-53) = 1166: x^2 - 22 x - 53 x + 1166

-53 x - 22 x = -75 x:

x^2 - 75x + 1166 =0

Thanks for the help, Guest! This sure helped a lot!

It says to leave it as a factored expresssion so I think you only need to say

(x-53)(x-22)=0

and leave it as that.